2021
DOI: 10.1002/jcb.29911
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lysyl oxidase expression in THP‐1 cell‐derived M2‐like macrophages

Abstract: Lysyl oxidase (LOX) is a copper‐containing enzyme and its overexpression in tumor tissues promote tumor metastasis through the crosslinking of extracellular matrix. Our previous report demonstrated that LOX expression is significantly increased in human leukemic THP‐1 cell‐derived M2‐like macrophages, and histone modification plays a key role in its induction. However, the rigorous mechanism of LOX regulation remains unclear. In this study, we investigated the role of functional transcription factors, hypoxia‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Regarding the induction of LOX in tumor-associated macrophages, we previously reported that JMJD3-mediated histone H3K27 demethylation plays a key role in its expression.‍ ( 71 ) Histone lysine demethylases, including JMJD3, are upregulated in several tumors.‍ ( 73 , 74 ) In addition, macrophage differentiation into tumor-associated M2 macrophages is regulated by JMJD3-mediated H3K27 demethylation.‍ ( 75 ) Our studies may help clarify the molecular mechanisms governing epigenetic LOX induction in the tumor microenvironment. We also demonstrated that hypoxia-inducible factor 1α (HIF1α), a well-known transcription factor induced in tumor tissues, is involved in LOX expression in tumor-associated macrophages.‍ ( 76 ) This is consistent with LOX expression increasing in the tumor microenvironment under hypoxic conditions.…”
Section: Role Of Cu-containing Secretory Enzymes In Tumor Progressionsupporting
confidence: 71%
“…Regarding the induction of LOX in tumor-associated macrophages, we previously reported that JMJD3-mediated histone H3K27 demethylation plays a key role in its expression.‍ ( 71 ) Histone lysine demethylases, including JMJD3, are upregulated in several tumors.‍ ( 73 , 74 ) In addition, macrophage differentiation into tumor-associated M2 macrophages is regulated by JMJD3-mediated H3K27 demethylation.‍ ( 75 ) Our studies may help clarify the molecular mechanisms governing epigenetic LOX induction in the tumor microenvironment. We also demonstrated that hypoxia-inducible factor 1α (HIF1α), a well-known transcription factor induced in tumor tissues, is involved in LOX expression in tumor-associated macrophages.‍ ( 76 ) This is consistent with LOX expression increasing in the tumor microenvironment under hypoxic conditions.…”
Section: Role Of Cu-containing Secretory Enzymes In Tumor Progressionsupporting
confidence: 71%
“…In different microenvironments, macrophages are polarized into two subtypes: classically activated macrophages (M1) or alternatively activated macrophages (M2) [ 23 , 24 ]. We used the human monocytic cell line THP-1, which is useful for studying monocyte/macrophage differentiation [ 25 , 26 ], and examined the expression levels of Rab44 compared with M1 markers, including IL-6, CD80, and NOS2, and M2 markers, including interleukin-10 (IL-10), CD206, and arginase. A real-time PCR analysis of mRNA levels revealed that Rab44 was transiently upregulated at an early phase in both M1 ( Figure 1 a, left panel and b) and M2 differentiation ( Figure 1 a, right panel and b).…”
Section: Resultsmentioning
confidence: 99%
“…However, upon Cu stimulation, exosomes secreted by MΦs increase angiogenesis mediated by endothelial cells in vitro and in vivo [222]. Ryuhei Takemoto and colleagues also found that overexpression of lysyl oxidase, a Cu-containing enzyme, in human leukemic THP-1cell-derived M2 MΦs promotes tumor metastasis [223]. Therefore, immune cell cuproptosis may have a multifaceted role in TME, and we are awaiting rational animal and cellular investigations to elucidate this role.…”
Section: Cell Fates In the Tmementioning
confidence: 99%